Experimental and theoretical studies on (2E,5E)-2,5-bis(2-methoxybenzylidene)cyclopentanone: Structural, electrochemical, spectroscopic features, solid-state interactions, molecular docking and adsorption studies onto 2D carbon nanomaterials - Veprim Thaçi; Arianit A. Reka; Nataša Ristovska; Ramiz Hoti; Avni Berisha; Jane Bogdanov (Macedonian Journal of Chemistry and Chemical Engineering, 2023)
A monocarbonyl analog of curcumin, (2E,5E)-2,5-bis(2-methoxybenzylidene)-cyclopentanone (B2MBCP), was prepared and characterized via spectroscopic methods (NMR, UV-Vis, FT-IR, and MS). Furthermore, density functional calculations were implemented to study the molecular structure and spectroscopic features, as well as adsorption properties. In addition, Hirshfeld surface and NBO theoretical analysis were carried out. The reduced density gradient (RDG) analysis via non-covalent interactions (NCI) and interaction region indicator (IRI) indicate the presence of extensive Van der Waals interactions. These interactions are classified in different contributions and energy stabilization from Hirshfeld surface analysis where the dominant type of contacts are H···H contacts. The molecular docking studies of B2MBCP with DNA revealed cooperative interactions that led to intercalation. The results from the cyclic voltammetry (CV) measurements agreed with the calculated energies of the frontier orbitals and the compound structure. Theoretical studies indicated that the relatively flat B2MBCP is adsorbed onto a graphene surface, with a significant adsorption energy of –41.19 kcal/mol. The results of this study provide a better overall picture of the properties of MAC with a cyclopentanone core and can be taken as a useful guide in the search for new biologically active compounds and new possible means of delivery.